The genus Neurigona Róndani, 1856 of Iran with the description of a new species from the Hyrcanian Mixed Forests biome (Diptera: Dolichopodidae). Issue 3 (3rd July 2022) - Kazerani, Farzaneh; Pollet, Marc; Zamani, Seyedeh Masumeh; Persson, Magnus
Abstract : This paper provides an overview of the Neurigona species found in Iran. During our studies in northern Iran four species of the genus Neurigona Róndani, 1856 have been collected, three of which for the first time in Iran: Neurigona helva Negrobov & Tsurikov, 1990, Neurigona pallida (Fallén, 1823) and Neurigona pseudolongipes Negrobov, 1987. One species, Neurigona persiana Pollet & Kazerani sp. n., proved new to science and is described here. An identification key to the males of the five known species of the genus Neurigona of Iran is given. http://www.zoobank.org/urn:lsid:zoobank.org:pub:28BC8A7E-391F-4758-B4B0-D2994A269DA8